Determinants of hospital delivery among mothers attending post-natal mother-baby clinic services from January to August 2020: a cross-sectional study of Busia, Uganda - Kizito Omona; Vincent Ritara Ojok (Cogent Public Health)
Background It is estimated that hospital delivery could reduce 16%–33% of maternal deaths. Despite the importance of delivering at health institutions, in many countries, mothers still prefer to give birth at home.Study aim The aim was to ascertain the determinants of hospital delivery among mothers attending post-natal mother-baby clinic services in Busia district.Methods We used analytical cross-sectional design, with mixed method approach. A sample of 385respondent mothers were interviewed using semi-structured questionnaires. Two Focus Group Discussions (FGD) were held with mothers.Results Hospital delivery was at 82.6%, with most mothers delivering from government hospitals (50.9%) and private hospitals. Place of residence of mothers was associated with Hospital Delivery (X2(1) = 1.515, p < 0.002). Mothers who lived in urban settings were 2.7times more likely to deliver from health facilities than mothers who lived in rural settings [cPR = 2.686, 95% CI (0.394–1.194)]. Husband’s educational level was a determinant of Hospital Delivery (X2(3) = 2.054, p < 0.006). Mothers whose husbands had primary education, secondary education and tertiary education were 2.2 times, 1.5 times and 1.3 times more odd of delivering from health facility respectively.Conclusion Hospital delivery in Busia was acceptably high. Women’s decision power enormously contributes to the choice of place of delivery.